Red blood cell depletion in small‐volume bone marrow processing using manipulation with third‐party red blood cells: A comparison of the performance of the COBE spectra and the spectra Optia systems. Issue 9 (5th August 2022) - Sumii, Yuichi; Fujii, Nobuharu; Fujii, Keiko; Kondo, Takumi; Urata, Tomohiro; Kimura, Maiko; Washio, Kana; Fujiwara, Hideaki; Asada, Noboru; Ennishi, Daisuke; Nishimori, Hisakazu; Matsuoka, Ken‐ichi; et al.
Abstract: Background: For pediatric recipients, red blood cells (RBCs) are added to bone marrow (BM) collections before low RBC volume BM processing using COBE Spectra (COBE) or Spectra Optia (Optia). However, the processing efficiency of this approach has not been evaluated. This study aimed to evaluate RBC depletion and nucleated cell subpopulation recovery rates in third‐party RBC‐manipulated BM products processed with the COBE or Optia. Study Design and Methods: We retrospectively collected data on RBC depletion from low RBC volume BM with third‐party RBCs (manipulated group) and on conventional large‐volume, BM (unmanipulated group) processing performed between September 2010 and December 2021. All procedures were performed using COBE or Optia. Results: The median residual RBC volume in the manipulated group was 9.5 ml in COBE and 2.5 ml in Optia ( p  = .01). The median total nucleated cell (TNC) and mononuclear cell (MNC) were comparable between the manipulated groups using each cell separator (TNC, 40.8 vs. 47.1%; MNC, 78.3 vs. 79.4%). The manipulation did not adversely affect TNC and MNC recoveries in either device. In addition, Optia achieved similar CD34 + cell recovery to that in large‐BM‐volume processing using the same device (147.5 vs. 184.5%, p  = .112). During a follow‐up period, neutrophil engraftment was achieved in all patients who received third‐party RBC‐manipulated grafts, and platelet engraftment was achieved in all cases, except one. Conclusion: The addition of third‐party RBC to low RBC volume BM collections from or for pediatric patients does not have any negative impact on either RBC depletion or hematopoietic cell recovery during processing with the widely used cell separator.